2021
DOI: 10.7717/peerj.10929
|View full text |Cite
|
Sign up to set email alerts
|

Genes for degradation and utilization of uronic acid-containing polysaccharides of a marine bacteriumCatenovulumsp. CCB-QB4

Abstract: Background Oligosaccharides from polysaccharides containing uronic acids are known to have many useful bioactivities. Thus, polysaccharide lyases (PLs) and glycoside hydrolases (GHs) involved in producing the oligosaccharides have attracted interest in both medical and industrial settings. The numerous polysaccharide lyases and glycoside hydrolases involved in producing the oligosaccharides were isolated from soil and marine microorganisms. Our previous report demonstrated that an agar-degrading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Genome‐based taxonomy assigned MAG21 to the uncultured taxon GCA‐2401725, whereas the majority of CAZymes possess homologs in Catenovulum spp. (Supplementary Table 4), recently described for pectinolytic capacities (Furusawa et al ., 2021). Growth of the Catenovulum isolate CCB‐QB4 on unsaturated galacturonate has been linked to GH28 and GH105 enzymes, which are also encoded by MAG21 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Genome‐based taxonomy assigned MAG21 to the uncultured taxon GCA‐2401725, whereas the majority of CAZymes possess homologs in Catenovulum spp. (Supplementary Table 4), recently described for pectinolytic capacities (Furusawa et al ., 2021). Growth of the Catenovulum isolate CCB‐QB4 on unsaturated galacturonate has been linked to GH28 and GH105 enzymes, which are also encoded by MAG21 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that strain CCB-QB4 T , possessed 183 glycoside hydrolases and 43 polysaccharide lyases including many alginate lyases in the genome [8]. Furthermore, in 2021, we found that CCB-QB4 T degraded and used uronic acid-containing polysaccharides, namely alginate, pectin, ulvan and gellan gum, as a carbon source [9]. Based on the polyphasic evidence in the current study, we propose that strain CCB-QB4 T represents a novel genus of the family Alteromonadaceae.…”
Section: Full-textmentioning
confidence: 99%
“…As for growth conditions, strain CCB-QB4 T was incapable of growing at 10 °C as compared to the other four strains [1–3, 7]. Our previous report demonstrated that strain CCB-QB4 T obligately required carbon sources, such as glucose and uronic acid-containig polysaccharides, in culture broth [9]. Similarly, MB supplemented with glucose was used to culture cells belonging to the genus Catenovulum [1–3].…”
Section: Full-textmentioning
confidence: 99%